Research proposal: evaluation of ART in adult patients (Journal of Applied Oral Science, 2006)
The primary objective of the Atraumatic RestorativeTreatment (ART) is to reduce the indication of tooth extraction by means of a low-cost technique. Considering the difficulties of Brazilian public services to meet the demand of care of the low-income population, with lack of care to the adult population, which usually receives only emergency care, the aim of this study is to assess the performance of high-viscosity glass ionomer cements accomplished by the modified atraumatic restorative treatment in one- and multiple-surface cavities, compared to the conventional restorative approach. It will be analyzed the clinical performance of the materials; cost (material and human resources); patient satisfaction with the treatment received; and preventive effect of treatment.